The conservative treatment of congenital scoliosis with hemivertebra: Report of three cases - Caredda, Matteo; Bandinelli, Diletta; Falciglia, Francesco; Giordano, Marco; Aulisa, Angelo Gabriele (Frontiers in Pediatrics, 2022)
Background Scoliosis is the most common congenital spinal disorder. The vertebral disorder can be due to failure of formation, segmentation or their combination. Complete formation failure results in hemivertebra that can cause asymmetrical growth and deformity. Statistically, 25% of congenital curves do not progress, 25% undergoes mild progression, while the remaining 50% evolve rapidly and require treatment. Hemivertebrae can be classified into 3 types: non-segmented, semi-segmented and fully-segmented. The fully segmented types are most likely to progress. Hemivertebra, in the thoraco-lumbar area, display faster rates of progression than those in the lumbar region. The treatment can be either conservative, or surgical. Usually, in rigid and short curves bracing is not recommended, whereas it can be useful for the treatment of secondary curves. Aim To evaluate the efficacy of bracing in congenital scoliosis with fully-segmented hemivertebra. Cases Presentation From our database, we identified three patients with congenital scoliosis due to hemivertebra. One was 6-years-old at the time of diagnosis and had a hemivertebra localized in L5, with a lumbar curve L1-L5 (S1). The other one was 10-year-old at the time of diagnosis and had a hemivertebra localized in L2 with a thoraco-lumbar curve T11-L4 (L5 sacralized). The last one was 3-years-old at the time of diagnosis and had a hemivertebra localized in L3 (in a six lumbar bodies), with a thoraco-lumbar curve T12-L4. Results The first patient was treated with a Milwaukee brace, the second with a Boston brace and the third with a PASB (Progressive Action Short Brace). The Cobb angles at the beginning were 23°, 53° and 25°, respectively. During the treatment, the Cobb angles were 22°, 35° and 15°, respectively. At the end of treatment, the Cobb angles were 18°, 45° and 12°, respectively. At long term follow-up, the curves were 20°, 45° and 12° Cobb angles, respectively. Conclusions Comparing our cases with those found in the literature we can confirm the ability of conservative treatment to change the natural history of congenital lumbar scoliosis. Conservative treatment can be considered a valid means to treat not only the patients with congenital scoliosis due to hemivertebra who refuse surgery.